Impact of contract farming on profits of smallholders: Evidence from cultivation of onion, okra, and pomegranate in India - Kumar, Anjani; Tripathi, Gaurav; Roy, Devesh; Joshi, Pramod Kumar; Karandikar, Bhushana (International Food Policy Research Institute, 2019)
This paper attempts to quantify the benefits of contract farming (CF) on farmers’ income and investigates the determinants of participation in CF. This is based on a survey of 1,331 farmers from Maharashtra State in India engaged in onion, okra and pomegranate cultivation. The study, using 2-Stage Least Squares method and propensity score matching approach, reveals that CF ensures higher returns for smallholders to the tune of Rs 14.5 per kilogram over independent farmers. Access to institutional credit, extension services, farm size, personal ownership of transport and migration significantly affected farmers’ participation in CF. The empirical evidence of the benefits of CF for high-value export commodities should encourage government policies to promote and scale up the use of CF in India.